Older learning engagement in the modern city. Issue 5 (2nd September 2016) - Lido, Catherine; Osborne, Michael; Livingston, Mark; Thakuriah, Piyushimita; Sila-Nowicka, Katarzyna
Abstract: This research employs novel techniques to examine older learners' journeys, educationally and physically, in order to gain a 'three-dimensional' picture of lifelong learning in the modern urban context of Glasgow. The data offers preliminary analyses of an ongoing 1500 household survey by the Urban Big Data Centre (UBDC). A sample of 1037, with 377 older adults aged 60+, was examined to understand older learner engagement in formal, in-formal, non-formal and family-learning contexts. Preliminary findings indicate that all forms of older learning participation are lower than younger and middle-age counterparts. However, there is a subset of 'actively ageing', socially and technologically engaged older adult 'learner-citizens', participating in educational, physical, cultural, civic and online activities (including online political discussions and boycotts). These older learners were more likely to be working, caretakers and report better health overall. Long-term disabilities were associated with less engagement in non-formal learning activities. Additionally, engaged older learners' GPS trails show more city activity than their matched non-learning-engaged counterparts. Place-based variables, such as feeling safe and belonging to the local area, moderated adult participation in learning activities. The full data-set will be accessible to researchers and the general public via UBDC, providing a complex data source to explore demographically diverse learners' within an urban context.